2021
DOI: 10.1186/s12876-021-02028-5
|View full text |Cite|
|
Sign up to set email alerts
|

The LUCID study: living with ulcerative colitis; identifying the socioeconomic burden in Europe

Abstract: Background Ulcerative colitis (UC) is an inflammatory bowel disease with increasing prevalence worldwide. Current treatment strategies place considerable economic and humanistic burdens on patients. The aim of this study was to determine the socioeconomic burden of UC in adult patients in European countries in a real-world setting. Methods In this retrospective, cross-sectional and observational pan-European study, patients with moderate or severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…In addition, at 2015 values, a higher cost per patient/year in CD (€3542) compared to UC was also observed in this study (€2088) [ 69 ]. Another recent pan-European study raised the mean annual direct medical, direct non-medical and indirect costs for UC in Spain up to €4551, €1321 and €3061 respectively, resulting in a mean annual total cost of €8934 [ 70 ]. This cost was the highest among the 10 participating countries of the study, with an overall mean annual total cost of €7854, all in 2019 prices [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at 2015 values, a higher cost per patient/year in CD (€3542) compared to UC was also observed in this study (€2088) [ 69 ]. Another recent pan-European study raised the mean annual direct medical, direct non-medical and indirect costs for UC in Spain up to €4551, €1321 and €3061 respectively, resulting in a mean annual total cost of €8934 [ 70 ]. This cost was the highest among the 10 participating countries of the study, with an overall mean annual total cost of €7854, all in 2019 prices [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] A further study focused on the costs and health-related quality of life (HRQoL) impacts of active UC and showed that there were high costs of care (direct and indirect) and adverse effects on HRQOL. 35 Combined with the results from our modelling, it would suggest that the optimised treatment pathway is highly likely to be cost-saving and therefore likely to be dominant over the standard treatment pathway. This is a potential area for further investigation and future extension of this current model.…”
Section: Discussionmentioning
confidence: 62%
“…In all cases, these analyses showed that the optimised therapy was the dominant treatment option (lower costs and higher-quality-adjusted life-years) 17–22. A further study focused on the costs and health-related quality of life (HRQoL) impacts of active UC and showed that there were high costs of care (direct and indirect) and adverse effects on HRQOL 35. Combined with the results from our modelling, it would suggest that the optimised treatment pathway is highly likely to be cost-saving and therefore likely to be dominant over the standard treatment pathway.…”
Section: Discussionmentioning
confidence: 97%
“…After publication of this article [ 1 ], the authors reported that the author name “Avedano” was incorrectly written as “Avendano”.…”
Section: Correction To: Bmc Gastroenterology (2021) 21:456 101186/s12876-021-02028-5mentioning
confidence: 99%